STUDIUM GENERALE AKADEMI MARITIM NUSANTARA BANJARMASIN DENGAN TEMA “FUNGSIMAHKAMAH PELAYARAN DALAM PENEGAKKAN KODE ETIK PROFESI DAN KOMPETENSI NAHKODA DAN/ATAU PERWIRA KAPAL” - Kamsariaty; Irnita Rosaria Santi; Hidayati Desy; Irtania (Akademi Maritim Nusantara Banjarmasin, 2023)
AbstractCourt means the body where the law is decided on a case or violation; court. Thus, a decision that is in accordance with thelaw cannot be contested after the decision is made. Orderly service and operation of facilities and infrastructure is still relativelylow, it turns out there are still many factors that contribute to this, such as weak awareness (awareness) of ship owners andcompanies in implementing effective safety systems and implementation in the field, ship seaworthiness which includesmore certification. In fact it is not supported by careful inspection, nor is the supervision carried out by the government regardingthe implementation (drilling) of shipping safety requirements inconsistent.The shipping court is a panel of experts who are under and responsible to the minister who is tasked with carrying outfurtherexaminations of ship accidents such as shipwrecks, fires, rapid take-offs and sinkings, which are examined bythe ship's crew,namely the captain and officers.The Studium Generale activity of the Banjarmasin Nusantara Maritime Academy with the theme The function of theshipping court in enforcing the professional code of ethics and competence of ship captains and/or officers, was givendirectly bythe resource person, namely Capt. Muhammad Ghazali, S.H., M.H., M.Mar. This is part of community service, so that thecadets who will later work in the shipping and port sector are equipped with the rules and functions provided by the resourceperson for this activity. This is able to protect all matters according to the rules of each incident. All causes and effects will havestages to solve the problem with research and actions adapted to these rules.Keywords: Stadium Generale, Voyages, Codes of Conduct